Community Structure and Distribution of Coleoptera Soil IPM and Non IPM Upland Vegetable Agricultural Areas in Two Villages in Kabanjahe - Arlen Hanel John (International Journal of Ecophysiology, 2021)
The concept of Integrated Pest Management (IPM) is an effort developed by the government in order to reduce the use of pesticides in the agricultural sector. In the development of agriculture in Kabanjahe, both Non-IPM (Non Integrated Pest Management) and IPM (Integrated Pest Management), research is needed to determine the community structure and distribution of soil fauna, including soil coleoptera, and to determine the effect of soil physical and chemical factors on soil coleoptera community structure in the highland vegetable farming area of Kabanjahe district. Karo Regency. Determination of sampling points in this study was carried out using the "purposive random sampling" method, in two agricultural areas, in two villages, namely Sumber Mufakat and Gung Negri, Non-IPM agricultural land areas and IPM agricultural areas. While the active coleoptera sampling of the soil surface was carried out using the Pit Fall Trap method, and the Quadratic and Hand Sorting methods for Coleoptera that live in the soil. The results showed that the number of types and population density of coleopteran soil was more / higher in the area. IPM agriculture. The highest density and relative density values in the research area were the genus Callosoma for the IPM and Non-IPM lands of Sumber Mufakat Village and the IPM of Gung Negri Village, while for the Gung Negri Non-IPM land the genus Scapidium and the genus Tenebrio.